2020
DOI: 10.1021/acsami.0c06080
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Demonstration of Dynamic Temperature-Dependent Behavior of UiO-66 Metal–Organic Framework: Compaction of Hydroxylated and Dehydroxylated Forms of UiO-66 for High-Pressure Hydrogen Storage

Abstract: High-pressure (700 MPa or~100 000 psi) compaction of dehydroxylated and hydroxylated UiO-66 for H2 storage applications is reported. The dehydroxylation reaction was found to occur between 150 -300 o C. The H2 uptake capacity of powdered hydroxylated UiO-66 reaches 4.6 wt% at 77 K and 100 bar, which is 21% higher than that of dehydroxylated . On compaction the H2 uptake capacity of dehydroxylated UiO-66 pellets reduces by 66% from 3.8 wt% to 1.3 wt%, while for hydroxylated UiO-66 the pellets show only a 9% red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 61 publications
3
17
0
Order By: Relevance
“…Such results confirmed both the successful synthesis of UiO-66 MOFs and the suitability of the mechanochemical approach for the modification of MOFs with metal entities. Even if the presence of both peaks related to the main crystallographic planes of UiO-66 indicated the retention of the crystal structure, certain amorphization occurred after the incorporation of higher Ni amounts in the sample [25,26]. Magnified XRD diffractograms (Figure 2B-E) revealed the typical characteristic pattern UiO-66 but with a clear decrease in crystallinity in the samples with 3 and 5% Ni.…”
Section: Resultsmentioning
confidence: 98%
“…Such results confirmed both the successful synthesis of UiO-66 MOFs and the suitability of the mechanochemical approach for the modification of MOFs with metal entities. Even if the presence of both peaks related to the main crystallographic planes of UiO-66 indicated the retention of the crystal structure, certain amorphization occurred after the incorporation of higher Ni amounts in the sample [25,26]. Magnified XRD diffractograms (Figure 2B-E) revealed the typical characteristic pattern UiO-66 but with a clear decrease in crystallinity in the samples with 3 and 5% Ni.…”
Section: Resultsmentioning
confidence: 98%
“…[13a] This is attributed to the collapse of the crystalline structure caused by the harsh activation condition, which in turn drastically diminishes the porosity of UiO-TF36 despite the most increased concentration of open metal sites. [16] In this regard, we chose an intermediate activation temperature of 200 8 8Cf or defectengineered UiO-66 throughout the following studies,e nsuring the presence of open metal sites formed by the partial removal of modulators as well as the maintained original porous structure.…”
Section: Resultsmentioning
confidence: 99%
“…82 Recently, attempt was made to study the effect of compaction on dehydroxylated and hydroxylated UiO-66 for hydrogen storage applications. 141 The gravimetric H 2 capacity of 4.6 wt% was and 3.8 wt% were obtained on powder hydroxylated and dehydroxylated UiO-66 respectively at 77K and 100 bar. However, a significant reduction was observed in the gravimetric hydrogen capacity of compacted dehydroxylated Zr-MOF compared to the hydroxylated compacts.…”
Section: Volumetric and Gravimetric H 2 Capacities Of Densified High Performing Mofsmentioning
confidence: 93%
“…However, high compression pressure of MOFs resulted in pellet with narrow pore apertures which yielded low volumetric and gravimetric H 2 useable capacities. 141,142 Recently, Chen et al 143 reported BET surface area of 7310 m 2 g −1 and volumetric BET surface area of 2060 m 2 cm −3 for NU-1501-Al. High gravimetric and volumetric storage capacities of 14.0 wt% and 46.2 g/L respectively were obtained under temperature and pressure swing of 77K/100 bar to 160K/5 bar.…”
Section: Mechanism Of Hydrogen Adsorption Of Mofsmentioning
confidence: 99%